Healthy diets, lifestyle changes and well-being during and after lockdown: longitudinal evidence from the West Midlands. Issue 2 (15th December 2022) - van Rens, Thijs; Hanson, Petra; Oyebode, Oyinlola; Walasek, Lukasz; Barber, Thomas M; Al-Khudairy, Lena
Abstract : Background: 'Lockdowns' to control the spread of COVID-19 in the UK affected many aspects of life and may have adversely affected diets. We aimed to examine (1) the effect of lockdowns on fruit and vegetable consumption, as a proxy for healthy diets more generally, and on weight and well-being, (2) whether any subgroup was particularly affected and (3) the barriers and facilitators to a healthy diet in lockdown. Methods: We conducted a mixed-method longitudinal study, involving an online survey of 1003 adults in the West Midlands, UK, 494 of whom were surveyed at two different points in time. Our first time point was during stringent COVID-19 lockdown and the second during a period of more relaxed restrictions. We asked quantitative questions about fruit and vegetable consumption; physical activity, sociodemographic characteristics, body mass index and well-being and qualitative questions about the reasons behind reported changes. Results: We find no evidence for decreased fruit and vegetable consumption during lockdown compared with afterwards. If anything, consumption increased by half a portion daily among women, particularly among those who normally have a long commute. This finding, combined with a significant increase in physical activity, suggests that behaviours were healthier during lockdown, consistent with higher self-reported health. However, well-being deteriorated markedly, and participants reported being heavier during the lockdown as well. Our qualitative data suggest that an abundance of resources (more time) supported higher fruit and vegetable consumption during lockdown, despite increased access issues. Conclusions: Our results may assuage concerns that lockdowns adversely affected diets. They may point to the impact of commuting on diet, particularly for women. We add longitudinal evidence to a growing body of literature on the adverse effect of lockdown on mental health.